Paulinove arcatovske bukve - Košir, Tone (Časopis za zgodovino in narodopisje, 2025)
On 1 July 2024, Elko Borko, President of the Medico-Historical Section within the Slovenian Medical Association, informed the author of this article that acquaintances had shown him a copy of a handwritten padar book (folk healing manuscript). In this way, another Slovenian manuscript healing book from 1876, previously unknown, has come to light – Paulin’s transcription (1876) of Lipič’s book (1810). In this article, the author presents some particularities of folk healing previously undocumented in Slovenia, such as incantations and medicinal herbs. Andrejka Žula, the former owner of the Paulinove arcatovske bukve (Paulin’s old folks healing manuscript), donated Paulin’s transcription to the University Library Maribor – the book has also been digitized.
Keywords: Arcatovske bukve; folk medicine; handwritten padar books (folk healing manuscripts); incantations; Janez Paulin; ljudsko zdravilstvo; medicinal herbs; Pavel Lipič; rokopisne padarske bukve; zagovori; zdravilna zelišča